Hubungan Usia, Pengetahuan, Tingkat Pendidikan dengan Kepatuhan Protokol Kesehatan - Rahmawati, Maulida (Tadulako University, 2023)
World Health Organization (WHO) declared the spread of COVID-19 as pandemic. Surabaya is the city with the highest positive cases in Indonesia. While reduce the transmission of COVID-19 virus, the government supervise to always comply health protocols. The implementation of policies in controlling COVID-19 cases will not be carried out properly if citizen still not comply health protocols. The purpose of this study was to determine the relationship between age, knowledge, and level of education with COVID-19 health protocol compliance in RT. 2 / RW. 4 Dukuh Setro Surabaya. This research is analytical use survey method with cross-sectional design. Samples were taken from the citizen based on the number of heads of families selected use accidental sampling. The amount of the samples were 52 respondents. Data was collected using an online questionnaire with google form for 3 weeks. Data analysis of this study use bivariate analysis chi square test in SPSS. The results obtained were 38 respondents (73.1%) adults and 14 respondents (26.9%) teenagers. There was 6 respondents (11.5%) with low knowledge, 29 (55.8%) respondents with moderate knowledge, 17 (32.7%) respondents with high knowledge. There were 9 respondents (17.3%) did not comply health protocol, 43 respondents (82.7%) complied health protocol. There was relationship between knowledge (0,003) and compliance health protocols in in RT. 2 / RW. 4 Dukuh Setro Surabaya. There was no relationship between age (0,668), education level (0,076), and health protocol compliance in RT. 2 / RW. 4 Dukuh Setro Surabaya.